The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/j.1349-7006.2002.tb02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Estrone and 17β‐Estradiol Reverse Breast Cancer Resistance Protein‐mediated Multidrug Resistance

Abstract: Breast cancer resistance protein (BCRP), an adenosine triphosphate-binding cassette transporter, confers resistance to a series of anticancer reagents, including mitoxantrone, SN-38 and topotecan. In the present study, we found that estrone and 17β β β β-estradiol potentiated the cytotoxicity of mitoxantrone, SN-38 and topotecan in BCRP-transduced K562 cells (K562/BCRP). These estrogens showed only a marginal effect, or none, in parental K562 cells. Estrone and 17β β β β-estradiol increased the cellular accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 11 publications
2
71
0
1
Order By: Relevance
“…8 In the original description, K562/BCRP cells did not have high P-gp expression. 16 During the course of selection we did not observe any induction of MDR1 mRNA or P-gp as shown in Figure 1B-C. Furthermore, we did not observe an increase in BCR-ABL mRNA or c-Kit protein as the result of mitoxantrone selection.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…8 In the original description, K562/BCRP cells did not have high P-gp expression. 16 During the course of selection we did not observe any induction of MDR1 mRNA or P-gp as shown in Figure 1B-C. Furthermore, we did not observe an increase in BCR-ABL mRNA or c-Kit protein as the result of mitoxantrone selection.…”
Section: Discussionmentioning
confidence: 57%
“…K562/BCRP cells were 5.5-fold resistant to mitoxantrone compared with wild-type K562 cells (Table 1), in agreement with the original report. 16 Selection with mitoxantrone (K562/BCRP-MX10) increased mitoxantrone resistance to 7.2-fold by the FDA/PI assay ( Figure 2A; Table 1), with comparable relative levels of resistance (11.8-fold) detected by the XTT assay ( Figure 2C; Table 2). Similarly, K562/BCRP-MX10 cells were more resistant to imatinib than K562 wild-type cells determined by both cytotoxicity assays ( To determine whether the resistance to imatinib is due to only BCRP overexpression, the effect of a specific inhibitor of BCRP, FTC, on resistance was studied in K562/BCRP-MX10 cells, with cellular viability assessed by the XTT assay (Figure 2C-D; Table 2).…”
Section: Sensitivity Of Bcrp-expressing K562 Cells To Mitoxantrone Anmentioning
confidence: 91%
See 1 more Smart Citation
“…Estrone and 17b-estradiol have been found to potentiate the cytotoxicity of SN-38, mitoxantrone, and topotecan in BCRP-transfected cells but not in a parental K562 line (Imai et al, 2002b). Estrone and 17b-estradiol also increased the cellular accumulation of topotecan in K562/BCRP cells.…”
Section: Expression Of Bcrp In Normal Tissuesmentioning
confidence: 92%
“…However, the sulphamates studied in this paper are derivatives of oestradiol, and many steroids, both unconjugated and conjugated to sulphate or glucuronide, including oestrogens, phytoestrogens and androgens, are substrates of BCRP Velamakanni et al, 2007). Studies have also shown that steroids and cholesterol, and steroid agonists and antagonists such as tamoxifen and diethylstilboestrol, can modulate the expression of BCRP without themselves being substrates (Imai et al, 2002;Janvilisri et al, 2003;Sugimoto et al, 2003;Morita et al, 2005;Pavek et al, 2005). A novel oestrogen response element (ERE) has been found in the human BCRP promoter (Ee et al, 2004a, b), although it has also been suggested that oestradiol post-transcriptionally downregulates BCRP (Imai et al, 2005).…”
Section: Discussionmentioning
confidence: 99%